The use of pattern participants relationships for integrating patterns: a controlled experiment. (20th October 2011) - Kamal, Ahmad Waqas; Avgeriou, Paris; Zdun, Uwe; Fayad, Mohamed E.; Singh, Shivanshu K.
SUMMARY Architectural patterns are often applied in combination with related patterns within software architectures. The relationships among architectural patterns must be considered when applying a combination of patterns into a system; for example the way the Model‐View‐Controller uses the Observer pattern to implement the change propagation mechanism needs to be carefully designed. However, effective integration of architectural patterns within software architectures remains a challenging task. This is because the integration of any two architectural patterns can take several forms. Furthermore, existing pattern languages define generic and abstract relationships between architectural patterns without going into detail about associations among the participants of architectural patterns. In this paper, we propose to address the pattern integration issue by discovering and defining a set of pattern participants relationships that serve the purpose of effectively integrating architectural patterns. Our findings are validated through a controlled experiment, which provides significant evidence that the proposed relationships support inexperienced designers in integrating patterns. Copyright © 2011 John Wiley & Sons, Ltd.